MORPHOMETRIC ANALYSIS OF SUBTENTORIAL TUMORS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The low incidence of astrocytomas of subtentorial localization in adults is one of the main reasons that the clinical manifestations of these neoplasms are little known [8]. The diagnosis of “cerebellar tumor” is established when the first clinical symptoms appear. The most common symptoms accompanying a cerebellar tumor are ataxia, headache and nausea [8]. Astrocytic tumors of subtentorial localization are clinically and histologically heterogeneous. They can have predominantly expansive (due to the cystic component) and invasive-infiltrative growth. The tendency toward invasive growth is more pronounced in relapses, and the tumor in such cases usually has a higher grade of malignancy. Due to the heterogeneity of the tumor tissue structure, certain difficulties often arise when diagnosing astrocytomas.